Francophone Rural Radio Training Course - Lalanne-Devlin, Laurence (Technical Centre for Agricultural and Rural Cooperation, 2007)
This synthesis of the francophone rural radio journalists training in Porto-novo, Benin, from the 18th-22th June 2007, mainly draws context and objectives, the course feed and its evaluation. Contents day by day with memos are described in annexes.